And what if? / Nadhirah A Azizsam and - A Azizsam, Nadhirah; Sain, Noridah (Academy of Language Studies, 2023)
Children’s storybooks have always been one of the most important tools for parents to help their children learn to read and write. In view of this, “And What If?” offers the same function as the currently available storybooks but with an advanced interactive game included. The chosen scope of this assignment is Creative Writing. As children are done reading the stories written, they can edit the plot of the stories by adding in their own ideas as well as answering the reflective activity game. The main objective of this unique storybook is to allow children to be more imaginative and hone their creative thinking skills in a more interesting way. To proceed with this idea, an online survey was carried out to obtain opinion and impression of the public regarding the project. Majority of the respondents agreed that this upcoming project will be beneficial for the children and are willing to invest in the storybook. The findings support the need to create a book that would add to the existing literature as well as assist parents who wish to have their children read more English materials.